Sistem Informasi Transaksi Berbasis Web pada Koperasi Tri Dasi Caka Tunggal di Desa Pegadungan - Yudhamanyu, Ida Bagus Agung Udaya; Luh Putu Cintya Prabandari; Komang Wilan Jaya (RESI : Jurnal Riset Sistem Informasi, 2025)
This research aims to design and implement a transaction information system at the Tri Dasi Caka Tunggal Cooperative in Pegadungan Village. This system development used the Waterfall development method. The methods used for data collection in this research were observation, interviews and literature study. In this research, the testing method uses a set of validation activities, with a black box testing approach. The results of the research show that the implementation of the Web-Based Transaction Information System at the Tri Dasi Caka Tunggal Cooperative in Pegadungan Village uses visual programming. System testing using the black box method from the test results was all successful.